Effectiveness Learning Management System (LMS) on Course Learning Outcomes in Islamic Higher Education Amidst the Covid-19 Outbreak - M. Mukhibat; Hestu Wilujeng (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2021)
Physical distancing policy because Covid-19 has entered schools, including Islamic colleges in Indonesia, which must revolutionize itself with an online learning policy. Meanwhile, public education courses' effectiveness is still minimal, raising questions about the impact and what media is used and its effectiveness on Course Learning Outcomes (CLO). Therefore, it tries to be explored in depth from the implementation of bold learning from the results of its evaluation. Research Survey descriptive equilibrium method, taking a sample from one population using a questionnaire as a tool and the primary data. The survey was conducted on 4000 out of 205 lecturers at IAIN Ponorogo. The research data were also taken from the evaluation reports of pink lessons from fifteen Indonesian Islamic higher education. The results showed that lecturers used at least 23 islands of media. The most used Whatsapp Group, namely 58.5%, google classroom 57%. The lecturer used various media to improve some student competencies: student reasoning by 43.4%, conveying ideas in 38.8% good categories, 33.8% good creative categories, and 45.6% good cooperation. Online learning and teaching in Islamic higher education IAIN Ponorogo Covid-19 pandemic table run quite effectively. Even though it is still a relative island, such as internet accessories, limited facilities, and student abilities, this does not flow from the spring table in front of the educators.